(untitled) (Third Sector Social Economic Review, 2023)
The effect of public relations studies in the successful functioning of communication processes between all units in health institutions is an undeniable reality. The role of public relations studies is increasing day by day, especially in strengthening the communication of health institutions with their target audiences and creating a strong image in their minds. In recent years, the great acceleration in the field of health and the growth of health institutions in this context have made public relations studies more prominent. Many articles, books and thesis studies have been conducted on this situation in the academic field. With the current study, the trends in thesis studies conducted in Turkey are discussed from a bibliometric perspective. In this study, it is aimed to reveal academic trends related to the concepts in question by examining master’s and doctoral theses related to public relations and health with bibliometric analysis.With the screening model, which is one of the qualitative research methods, 21 postgraduate thesis studies obtained from the national thesis search center of YÖK were analyzed. As a result of the findings, it was concluded that the theses on the relationship between public relations and health increased in the last ten years, these theses emerged in the department of public relations and publicity and in the departments of relations, therefore, there were no postgraduate thesis studies on the relationship between public relations and health in health-related departments. has been reached. It has been seen that the majority of theses consist of master’s theses, and the concept of ""public relations"" stands out in the context of keywords.